1988
DOI: 10.1295/polymj.20.1031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Periodic Copolymers: Alternating Copolymerization of Propylene with Methyl α-Chloroacrylate

Abstract: ABSTRACT:To synthesize a series of periodic copolymers containing simple ll(-olefins, the alternating copolymerization of propylene (P) with methyl ll(-chloroacrylate (MCA) was examined. An alternating P-MCA copolymer could hardly be obtained by conventional procedures where organoaluminium chlorides alone were used as complexing reagents. The addition of vanadium oxytrichloride or acetylacetonate as the second catalyst provided the well-defined alternating P-MCA copolymer. The P(P-alt-MCA) was found to have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This may be the case because the periodic copolymers usually have quite different glass transition characters in comparison with statistical copolymers. Yokota reported that the T g of poly[MCA‐Pr] (alternating copolymer of methyl α‐chloroacrylate with proplene) increased from 56 to 76°C when the propylene unit was substituted by more flexible units of EE (poly [MCA‐E‐E]) 15, 16. For statistical copolymers, it has also been reported that introducing a more flexible unit of vinylidene chloride could increase the T g of poly(methyl acrylate) as much as 32.5°C 17.…”
Section: Resultsmentioning
confidence: 99%
“…This may be the case because the periodic copolymers usually have quite different glass transition characters in comparison with statistical copolymers. Yokota reported that the T g of poly[MCA‐Pr] (alternating copolymer of methyl α‐chloroacrylate with proplene) increased from 56 to 76°C when the propylene unit was substituted by more flexible units of EE (poly [MCA‐E‐E]) 15, 16. For statistical copolymers, it has also been reported that introducing a more flexible unit of vinylidene chloride could increase the T g of poly(methyl acrylate) as much as 32.5°C 17.…”
Section: Resultsmentioning
confidence: 99%